Pengaruh Beban Kerja Terhadap Kinerja Pramugraha: Studi Kasus Di Marbella Suites Bandung - Kalsum, ER Ummi (Politeknik Pariwisata NHI Bandung, 2018)
This research is associative research with a causal relationship based on the explanation level, that is how this research is explained. Associative research is research in which the aim is to find a relationship or influence between two or more variables that serve to explain, predict and control certain symptoms. While the causal relationship is the cause-effect relationship, where X Influences Y. This research when viewed from the goal is applied research or applied research, which is